INDIGENOUS TECHNOLOGIES FOR MEAT PROCESSING AND PRESERVATION IN NIGERIA - A REVIEW - Apata, E. S.,; Olanloye, S. A.,; Apata, O. C.,; Olaleye, O. O.,; Kamarudeen, K. R., (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
Nigeria is confronted with food security challenges despite the fact that Nigeria is a country with greater arable land and numerous animals to feed it growing population. However, the country remains the most impoverished in food security as millions of people in Nigeria lack adequate food, especially animal protein for a healthy and active life. There is consequently an urgent need to look for more practical ways to confront these challenges. One of such ways is the promotion and utilization of indigenous knowledge of food processing, preservation and storage. Nigeria is blessed with various types of food produce and animal species. It also possesses diverse indigenous technological systems for processing and preservation of these food products. This article reviewed meat processing methods and efficiency of meat preservation technologies, quality and safety of processed meat products and possible improvement. The meat which is not freely exposed to the sun, and better handling practices would help in developing a fresh meat export trade toward the larger towns in the North and South. Several studies revealed that meat drying, smoking and salting still remains the main methods of meat preservation in Nigeria as over 70% of meats are dried, smoked and salted. The quality of smoked meat from Nigeria has been found to be within acceptable quality limits specific by various regulatory agencies. Meat handling, processing and preservation are reviewed in this article to provide information for improvement of cultured meats management and practices in Nigeria. Consumer protection in this review was considered the major priority before any other consideration.